Hungarian Monitoring, 17 January 1988 . [Magyar rádiófigyelő], 1988. január 17 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Soviet conditions on nuclear weapons reduction - West German-Polish relations - Israeli forces are intensifying their presence in the occupied territories - Soviet-German negotiations - Argentina: Colonel Aldo Rico has fled Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) against multi-party system, emphasizes the Party's leading role - Writers' Association relations with the government - Background reports on the Seoul Olympic Games Külpolitika: - Nukleáris fegyverzetcsökkentés - Szovjet feltételek - Nyugatnémet-lengyel kapcsolatok - Izrael fokozza erőit a megszállt területeken - Szovjet-német tárgyalások - Argentína: Aldo Rico ezredes szökésben Belpolitika: - MSZMP ellenzi a többpárti rendszert, hangsúlyozza a párt vezető szerepét - Írószövetség viszonya a kormánnyal - Háttérriportok a szöuli olimpiával kapcsolatban